Аналіз структур вхідних даних в задачах індуктивного моделювання - Щербакова, Н.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
One of the most important steps towards developing an integrated environment of storing and handling information in the tasks of inductive modeling is the design of the integration of external data in the repository. The article discusses key issues arising at this stage, including the structure of input data analyzed by various parameters.